A Survey of some Medicinal Plants for Fungal Diseases from Osmanabad District of Maharashtra State - S.L. Korekar, S.P. Chavan and (Recent Research in Science and Technology, 2011)
The present investigation was carried out in various Talukas of Osmanabad District, India during the years 2008 & 2009. In the present research we have selected commonly found and economically important three medicinal plants viz. Aloe vera (L.) Burm. F, Datura metel L. and Withania somnifera (L.) Dunal from various locations of Osmanabad District for the survey of fungal diseases. Plants were examined In situ for disease symptoms as well as samples being collected for laboratory analyses. Fungi were identified using morphological characteristics, and where necessary with molecular techniques. The survey resulted in a range of fungi identified from the target plants. Common diseases on all the three plants were leaf spots, leaf blight and leaf rust causes harmful effects on medicinal value of the plant parts. Alternaria spp. was attacked on Aloe and Datura leaf while Cercospora withaniae causes leaf spot diseases of Withania. Other fungi observed were Fusarium solani, Aspergillus niger, Penicillium spp., etc. These found to be very harmful for the medicinal uses of the plant parts and may be adversely affect to the body.